KONFLIK INTERPERSONAL DALAM JEMAAT MULA-MULA: TANTANGAN PASCA YESUS BAGI PARA RASUL - Zein Marshellin Rante; Lindayani, Friska Yani Baaka (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study discusses interpersonal conflicts in the early church and the challenges faced by the apostles after Jesus. Interpersonal conflict in the church context can affect congregational life, church ministry, and bonds between congregations. This study aims to understand how the apostles dealt with the conflict and the biblical principles that can be applied in managing interpersonal conflict. In this study, it was found that interpersonal conflicts in the early congregation were caused by differences in theological, cultural, linguistic, socio- economic, political, personality, and character views. The apostles displayed tact, love, and humility in the face of conflict. They encourage open communication, understanding, forgiveness, and peaceful solutions. The apostles also built solidarity and togetherness among church members and developed leaders who were able to manage conflicts with wisdom and justice. A biblical perspective provides important principles for dealing with interpersonal conflict, including forgiveness, cooperation, speaking truth and love, humility, resolving conflict personally, and avoiding unnecessary conflict. This research provides insights for church leaders and congregation members in dealing with conflicts in today's church community. By applying the lessons learned from the apostles' responses and Bible principles, it is hoped that today's congregations can manage interpersonal conflicts well and create a peaceful, harmonious, and loving environment within the church fellowship.